Corporate governance, tax avoidance, and corporate social responsibility: Evidence of emerging market of Nigeria and frontier market of Pakistan - Nasir Khan; Ogunleye Oluwasegun Abraham; Adegboye Alex; Damilola Felix Eluyela; Iyoha Francis Odianonsen (Cogent Economics & Finance, 2022)
The main purpose of this study is to shed light on the relationship between corporate governance, tax avoidance, and corporate social responsibility disclosure in emerging and frontier markets Nigeria and Pakistan, respectively. The current study employs a unique set of datasets about 91 companies from the Nigeria Stock Market and 121 companies from the Pakistan Stock Market for the period of ten years from 2011 to 2020. We used a fixed effect regression model to analyze the panel data. From the analysis, we find that corporate social responsibility is positively and significantly associated with tax avoidance in the case of Nigeria. Meanwhile, CSR has a positive but insignificant effect on tax avoidance in the case of Pakistan. However, board nationality shows a positive and insignificant impact on CSR, whereas board independence, board ownership, board diversity, and board size are negatively and insignificantly associated with CSR in Nigerian firms. In the case of Pakistani firms, both board ownership and board independence are positively and insignificantly associated with CSR, though board nationality has a negative but significant relationship with CSR, and board diversity and board size are negatively and insignificantly related to CSR. The paper's findings have vital implications for policymakers, academics, and capital market users in the frontier and emerging economies. It has better significance for the government and companies to pay attention to CSR.
Keywords: 330; Corporate social responsibility; corporate governance; tax avoidance; fixedeffect regression models; panel data; emerging and frontier markets